Clinical Evaluation of Ocular Foreign Bodies (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background : Ocular foreign body can affect at any age as well as in both genders. Foreign body introductionin eye leads to various disturbances which can create significant health related problem. The study of theocular foreign body gives unparalleled opportunities in reducing morbidity as well as for realizing significantsavings for both financial as well as human terms.Material and Method: This prospective study was conducted in ophthalmology department at of Krishnahospital, Karad, Hundred patients with ocular foreign bodies were included in study with consideration ofinclusion and exclusion criteria.Results : A study of 100 subjects showed that incidence of extraocular foreign bodies is very commoncompared to intraocular foreign bodies. Amongst that, corneal foreign bodies found to be have highestincidence. Commonest foreign body observed -iron particle (43%) and thorn/vegetative material (38%).Average age-40 years. Males are having higher incidence than females. Average interval between incidentand intervention – 2.6 days (day 0 to day 10). Amongst the affected population, farmers and welders aremaximum in number.Conclusion : Though incidence of intraocular foreign body is very less, it has bad prognosis in relation withvision as well as progresses to endophthalmitis. Early visit to ophthalmologist showed better prognosis andthus visual outcome specially in cases of vegetative foreign body in which delayed treatment lead to furthercomplications.